Serum Homocysteine as a Prognostic Marker in Liver Cirrhosis - Dr. Mudassir Hussain; Dr. Potrick Faizan Jalal; Dr. KP Singh; Dr.Mahipalpuri Singh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Liver cirrhosis is a global health burden with significant diagnostic and prognostic challenges. Serum homocysteine, a sulfur-containing amino acid, is increasingly recognized as a marker of endothelial dysfunction and liver impairment. Aims: This study aims to investigate serum homocysteine levels as a prognostic indicator in liver cirrhosis. Methods: A cross-sectional analysis of 50 patients was conducted, showing a strong correlation of homocysteine with MELD and CTP scores. Results: These findings suggest serum homocysteine as a valuable prognostic biomarker in liver cirrhosis. Conclusion: Serum homocysteine levels show a significant correlation with the severity of liver cirrhosis. As a non-invasive marker, it holds promise for prognostication in cirrhotic patients. Future longitudinal studies are warranted to further validate its utility.